Immobilizing bacteria in expanded perlite for the crack self-healing in concrete. (1st September 2017) - Zhang, Jiaguang; Liu, Yuanzhen; Feng, Tao; Zhou, Mengjun; Zhao, Lin; Zhou, Aijuan; Li, Zhu
Graphical abstract: Highlights: EP particles as a novel bacteria carrier on crack-healing in concrete was studied. EP particles exert more positive effects on the healing capacity over EC particles. Microstructures of the mineral precipitations on the crack surface were analyzed. Completely healed crack widths were maximized in EP-B specimens. Abstract: Immobilization has been reported to be an efficient approach for bacteria-based self-healing concrete to maintain the high-efficiency mineral-forming capacity of incorporated bacteria over a period of time. However, the relatively high-cost, local unavailability, and low adsorption capacity of the current bacteria carriers make them impractical for potential implementation in large-scale concrete structures. In this study, the feasibility of expanded perlite (EP) as a novel bacteria carrier on quantifying cracks-healing in concrete via immobilization of Bacillus cohnii was demonstrated. The effects of two other self-healing techniques, i.e., direct introduction of bacteria and expanded clay (EC) immobilized bacteria, on the efficiency of crack-healing were also investigated. Experimental results showed that specimens incorporated with EP-immobilized bacteria exhibited the most efficient crack-healing after each healing time. The values of completely healed crack widths were up to 0.79 mm after 28 days of healing, which is larger than the value of 0.45 mm for specimens incorporated with EC-immobilized bacteria. Field emission scanning electron microscope (FESEM) and X-ray diffraction (XRD) analysis confirmed that mineral precipitations on their crack surfaces are calcite crystals. The findings obtained in this study may provide a scientific basis for the potential implementation of expanded perlite, as a new microorganism carrier, in bacteria-based self-healing concrete.